The relationship between Islamic religiosity and residents’ perceptions of socio-cultural impacts of tourism in Iran: Case studies of Sare’in and Masooleh - Zamani-Farahani, H.; Musa, G. (Elsevier, 2012)
Religion is known to influence people’s perception and behaviour. This study explores the influence of Islamic religiosity (measured on dimensions of ‘Islamic Belief’, ‘Islamic Practice’, and ‘Islamic Piety’) on the perceived socio-cultural impacts of tourism among residents in two tourist areas in Iran. The results showed that respondents both possessed a high level of Islamic Belief and perceived socio-cultural impacts of tourism positively. The propositions which stated that ‘Islamic Belief’ and ‘Islamic Practice’ have negative relationships with the perceptions of socio-cultural impacts of tourism are not supported. However levels of ‘Islamic Piety’ had statistically significant variations relating to potential changes in infrastructure, life quality and cultural practices that may be due to tourism. This paper also discusses the implications of its findings.